Does age matter to influence self-efficacy: review of related Literature - Priyadharsan, S.; Saravanabawan, A. (Journal of Management, 2021)
This article reviews the research that focused on the relationship between age and self- efficacy by reviewing the previous studies carried out in the age and self-efficacy knowledge. Self-efficacy refers to a person’s belief in their own abilities to accomplish a specific task and produce results. The main theme of this research is whether there is a difference between older and younger employees in terms of self-efficacy and age. The objective of this review is to identify the influence of age on self-efficacy and to identify the influence of age on the training and computer knowledge of employees. In the methodological part, the researcher considers the effects of training and computer knowledge on the self-efficacy of employees. Although older employees have an age- based experience that encourages their greater productivity, younger employees are more enthusiastic, ambitious, innovative, and involved in their work. The results of the review reveal that age influences self-efficacy. The self-efficacy of older employees can be improved through education, attitudes, appropriate training, work intervention, practices, and experience.
Keywords: Age; Attitudes; Self-Efficacy; Job Performance